Experimental investigation of surface roughness and cutting ratio in a spraying cryogenic turning process. Issue 5 (3rd September 2019) - Saliminia, Aref; Abootorabi, Mohammad Mahdi
Abstract: Surface roughness is one of the most common criteria indicating the surface finish of the part, which depends on various factors including cutting parameters, geometry of the tool, and cutting fluid. One of the goals of using cutting fluids in machining processes is to achieve improved surface finish. In addition to high costs, commonly used cutting fluids cause dermal and respiratory problems to the operators as well as environmental pollution. The present article aims at investigating the effect of spray cryogenic cooling via liquid nitrogen on surface roughness and cutting ratio in turning process of AISI 304 stainless steel. Through conducting experimental tests, the effects of cutting speed, feed rate, and depth of cut on surface roughness and cutting ratio have been compared in dry and cryogenic turning. A total number of 72 tests have been carried out. Results show that cryogenic turning of AISI 304 stainless steel reduces surface roughness 1%–27% (13% on the average), compared to dry turning. The obtained results showed that the cutting ratio in cryogenic turning is averagely increased by 32% in comparison with dry turning, also that chip breakage is improved in cryogenic turning.